Jabar Hattrick, Team West Java’s Victory in the XXI National Sports Week: A Framing Analysis - Putranto, Teguh Dwi; Putera, Kevin Sanly (Journal of Social Dynamics and Governance, 2025)
Jawa Barat (West Java/Jabar) achieved a "Hattrick" when the West Java team was announced as the overall champion at the XXI National Sports Week (PON) in Aceh and North Sumatra. The XXI National Sports Week in 2024 also achieved a "hat-trick" for West Java, following the West Java team's overall championship at the previous events, namely the XIX National Sports Week in 2016 (West Java) and the XX National Sports Week in 2020 (Papua). XXI National Sports Week also made a "hat-trick" for West Java, after the West Java team also became the overall champion at the previous National Sports Week, namely at XIX National Sports Week (West Java) and XX National Sports Week (Papua). This study aims to determine the framing of the news of the victory of the West Java team at the PON XXI/2024. The method used in this research is Robert N. Entman's framing analysis. The unit of analysis used in this research is the news on online media, which includes Detik.com and Kompas.com after the 2024 National Sports Week after September 20, 2024. Based on the search results, Kompas.com reported more about the victory of the West Java team coming from two sides, administrators and athletes. While on Detik.com, the victory of the West Java team was more focused on the struggle from the athlete's side. Framing related to the victory of the West Java team at the 2024 National Sports Week is supported by the existence of sports management, an optimistic attitude, consistency, not complacency, especially for athletes.